2021
DOI: 10.1038/s41598-021-99151-w
|View full text |Cite|
|
Sign up to set email alerts
|

Co-contraction of ankle muscle activity during quiet standing in individuals with incomplete spinal cord injury is associated with postural instability

Abstract: Previous findings indicate that co-contractions of plantarflexors and dorsiflexors during quiet standing increase the ankle mechanical joint stiffness, resulting in increased postural sway. Balance impairments in individuals with incomplete spinal cord injury (iSCI) may be due to co-contractions like in other individuals with reduced balance ability. Here we investigated the effect of co-contraction between plantar- and dorsiflexors on postural balance in individuals with iSCI (iSCI-group) and able-bodied indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…A previous study investigated the adaptation of the ankle and ankle-hip strategies based on the mean magnitude-squared coherence between the trunk-leg accelerations (Noamani et al, 2020 ). Another study measured the effect of co-contraction of the plantar and dorsiflexor muscles on the postural sway using a computational simulation study (Fok et al, 2021 ). Owing to the high accuracy of the instrumentation used in this study in capturing angular velocity at the ankle joint, future studies should include frequency and simulation analyses to investigate the effects of the ankle and hip strategies in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated the adaptation of the ankle and ankle-hip strategies based on the mean magnitude-squared coherence between the trunk-leg accelerations (Noamani et al, 2020 ). Another study measured the effect of co-contraction of the plantar and dorsiflexor muscles on the postural sway using a computational simulation study (Fok et al, 2021 ). Owing to the high accuracy of the instrumentation used in this study in capturing angular velocity at the ankle joint, future studies should include frequency and simulation analyses to investigate the effects of the ankle and hip strategies in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate, the muscle might activate even more motor units to regain control. However, it has been shown that individuals with iSCI seem to maintain good control of the available motor units, despite a limited number of muscle fibers in their lower leg muscles [ 41 ]. Therefore, our results could indicate that individuals with iSCI show a relatively higher effort and activity in their thigh muscles to compensate for the limited number of muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…These EMG signals were measured using an EMG amplifier (Bagnoli, Delsys Inc., Boston, MA, USA) and sampled at 2 kHz using a data acquisition system (PowerLab 16SP, ADInstruments Inc., Colorado Springs, CO, USA) synchronized with the other sensor signals mentioned above. We selected this sampling frequency based on our previous papers using EMG signals [21,22].…”
Section: Experimental Procedures 241 Studymentioning
confidence: 99%